Development and validation of a basement membrane inflammatory response gene signature in lung adenocarcinoma - Shilei Liu; Fengchu Liao; Qingming Xie; Sai Zhang; Dehong Tan; Xuesheng Xu; Jianlan Luo; Xujun Liang; Pengfei Zhang (Scientific Reports)
Abstract Inflammatory cell infiltration within the tumor microenvironment compromises the basement membrane’ integrity, contributing to chemotherapy resistance and distant metastasis. This study investigates the interplay between inflammatory responses and basement membrane-related genes (BMIRGs) in lung adenocarcinoma (LUAD). With datasets from the TCGA and GEO databases, the BMIRG risk-score model was developed based on univariate Cox regression and a LASSO-Cox regression model. Nine genes were identified as comprising the BMIRG signature. Using this signature, we developed the predictive models, including BMIRG risk scores and nomogram and Cox regression models. Stratifying patients into high-and low-risk groups based on BMIRG risk scores revealed a more favorable prognosis in the latter group. Additionally, the signature exhibited correlations with drug sensitivity, immunotherapy response, infiltration of multiple immune cells and inflammatory factors in microenvironment. The role of one BMIRG signature, CCL20, was further validated using in intro experiments and tissue samples from Chinese patients with LUAD. Functional experiments revealed that inhibiting CCL20 attenuated cell migration in both A549 and H1299 cells. Immunohistochemistry and Western blot analyses demonstrated that CCL20 protein levels were significantly elevated in LUAD tissues compared to adjacent non-tumor tissues and also associated with tumor the TNM stage. High CCL20 expression was also linked to shorter overall survival. In conclusion, the BMIRG signature is a robust predictor of survival and offers a valuable clinical tool for LUAD management. Moreover, CCL20 emerges as a potential diagnostic and therapeutic target, given its high expression in LUAD patients and association poorer prognosis.